Solute redistribution and phase stability at FeCr/TiO2−x interfaces under ion irradiation. (1st May 2015) - Xu, Y.; Aguiar, J.A.; Yadav, S.K.; Anderoglu, O.; Baldwin, J.K.; Wang, Y.Q.; Valdez, J.A.; Misra, A.; Luo, H.M.; Uberuaga, B.P.; Li, N.
Abstract: Cr diffusion in trilayer thin films of 100 nm Fe–18Cr/125 nm TiO2− x /100 nm Fe–18Cr deposited on MgO substrates at 500 °C was studied by either annealing at 500 °C or Ni 3+ ion irradiation at 500 °C. Microchemistry and microstructure evolution at the metal/oxide interfaces were investigated using (high-resolution) transmission electron microscopy, energy-dispersive X-ray spectroscopy and electron energy loss spectroscopy. Diffusion of Cr into the O-deficient TiO2 layer, with negligible segregation to the FeCr/TiO2− x interface itself, was observed under both annealing and irradiation. Cr diffusion into TiO2− x was enhanced in ion-irradiated samples as compared to annealed. Irradiation-induced voids and amorphization of TiO2− x was also observed. The experimental results are rationalized using first-principles calculations that suggest an energetic preference for substituting Ti with Cr in sub-stoichiometric TiO2 . The implications of these results on the irradiation stability of oxide-dispersed ferritic alloys are discussed.